2005
DOI: 10.1002/fut.20178
|View full text |Cite
|
Sign up to set email alerts
|

Futures and options expiration-day effects: The Indian evidence

Abstract: VIPULThis study examines the effect of expiration of options and futures on price, volatility, and volume of the underlying shares. The values of these variables 1 day prior to expiration, on the day of expiration, and 1 day subsequent to expiration are compared with those 1 and 2 weeks before and after the corresponding day with the use of the Wilcoxon matched-pairs signed-ranks test. The underlying share prices tend to get marginally depressed a day prior to expiration and to strengthen significantly a day a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Chow et al (2003) could not identify any such effects in the Hong Kong stock market. Edwards (1988), Arago and Fernandez (2002), Vipul (2005), and Gurgul and Suliga (2020) all detected higher price volatility of futures contracts near expiration. By contrast, Schlag (1996) and Bollen and Whaley (1999) could not obtain such evidence for the German stock market and the Hong Kong Futures Exchange respectively.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Chow et al (2003) could not identify any such effects in the Hong Kong stock market. Edwards (1988), Arago and Fernandez (2002), Vipul (2005), and Gurgul and Suliga (2020) all detected higher price volatility of futures contracts near expiration. By contrast, Schlag (1996) and Bollen and Whaley (1999) could not obtain such evidence for the German stock market and the Hong Kong Futures Exchange respectively.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Pope and Yadav (1992) found negative returns as well as higher trading volumes on expiration days in the UK stock market, whilst Stoll and Whaley (1997) and Hsieh (2009) provided evidence of price reversals in the Australian and Taiwanese stock markets. Vipul (2005) found that the underlying assets tend to exhibit negative returns the day before expiration, but significant reversal happens on the next trading day. Y.F.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kamaiah and Sakthivel [13] investigated the impact of stock futures expiration on the spot market in the NSE and observed positive abnormal returns and volumes on days before the expiry day. Vipul [14] analyzed the expiry day impact in the Indian stock market. 14 equity shares of different sectors were considered for the study and it found that share prices have fallen the day before the expiration day and has risen significantly the day after the expiration day.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Such options are therefore excluded from the study. Similarly, options with less than two days to maturity are removed as their prices may get distorted due to the expiration day effects [27].…”
Section: Data Screeningmentioning
confidence: 99%